TANGGUNG JAWAB PLATFORM E-COMMERCE DAN MERCHANT TERHADAP KONSUMEN DARI PEREDARAN KOSMETIKA TANPA IZIN EDAR (CONTOH PUTUSAN NOMOR 142/PID.SUS/2020/PN.JKT.BRT) - Felicia Ade Putri; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2020)
The rise of cosmetics distribution in Indonesia, has a good and bad impact on consumers. In this modern era, cosmetics can also be circulated via the internet, one of which is through e-commerce platforms. So that business actors in the e-commerce platform or it can be called merchants can distribute cosmetics even though they do not have a distribution license from the authorized agency. Cosmetics without distribution permits can be distributed through the e-commerce platform freely, without requiring a permit as stipulated by the minister or BPOM. For example, use Decision Number 142/Pid.Sus/2020/PN.Jkt.Brt, where merchants who distribute cosmetics without distribution permits through several e-commerce platforms in Indonesia. But what about the responsibilities of e-commerce platforms and merchants as business actors because they have harmed consumers by distributing cosmetics that do not have a distribution license. The purpose of this study is to find out more about the responsibilities of e-commerce platforms and merchants. In order to answer these problems, a normative research method is used and uses two approaches, namely the statutory approach and the case approach, with deductive analysis techniques. The results of this study indicate the need for strict supervision of cosmetics circulating through the e-commerce platform circulated by merchants as business actors providing products to consumers.